Paradoxes and Dilemmas within Business Models of Digital Platforms: A Case Study on an Innovation Platform - Waldmann, Martin (My University, 2020)
Digital platforms with their distinct characteristics offer several competitive advantages compared to traditional business models. Digitalized products and services, a modular platform architecture, the possibility to harness third-party expertise, and network effects enable extraordinary growth and foster innovation. However, all these characteristics do not have purely positive effects on a plat-form’s value but rather are subject to paradoxical tensions. In order to maintain a healthy platform ecosystem that generates value for all its members, participants must acknowledge and actively manage the paradoxes. This includes, for example, making trade-offs between flexibility and stabil-ity, competition and cooperation, openness and variety. Decisions in this context eventually have ambiguous effects on the content quality, the degree of innovation and generativity, and the ability to appropriate value. Thus, the paradoxes must be well understood and strategies must be constantly adjusted to changes in the technological and economic environment. The goal of this thesis was to identify paradoxes that exist within platform businesses and related management strategies. For that purpose, first, the literature has been reviewed and structured using the grounded theory method. This process brought forth several tensions that can be grouped into five categories: platform value, complement development, platform architecture, short-term vs. long-term focus, and role and iden-tity. By interviewing several stakeholders involved in the development of a digital innovation plat-form, more practical insights could be gathered. The expert interviews showed that many of the ten-sions found during the grounded theory review are present in the day to day work of various stake-holders and significantly influence their decision-making. In order to cope with them all parties must acknowledge their existence and continually reassess and adjust their strategy.